The Moderating Effect of Managerial Ownership on the Relationship between Product Market Competition based on the HH Index and the Cost of Equity Capital - Sajad Bahri; Hamedeh Jahangiri (New Applied Studies in Management, Economics & Accounting, 2023)
The target of this study, investigating the moderating effect of managerial ownership on the relationship between competition in the product market, is based on the Herfindahl-Hirschman index and the cost of capital of companies listed on the Tehran Stock Exchange. The statistical sample includes 82 companies during the period from 2011 to 2020. Hypotheses testing was performed using linear regression and panel data along with the fixed method, using Eviews 9 software. The results indicate that competition in the product market has an inverse and significant relationship with the cost of equity capital, but managerial ownership has no effect on the relationship between competition in the product market and the cost of equity capital.